Inflammatory Cell Composition and Immune-Related microRNA Signature of Temporal Artery Biopsies From Patients With Giant Cell Arteritis - Bolha, Luka; Hočevar, Alojzija; Suljič, Alen; Jurčić, Vesna (Frontiers in Immunology, 2021)
Objectives: The aim of this study was to quantitatively assess distinct immune cell subsets comprising inflammatory infiltrate in temporal artery biopsies (TABs) from patients with giant cell arteritis (GCA), and to link the obtained histopathological data with expression profiles of immune-related microRNAs (miRNAs). Methods: The study included 68 formalin-fixed, paraffin-embedded TABs from treatment-naïve patients, including 30 histologically positive GCA and 16 negative GCA TABs, and 22 control non-GCA TABs. Quantitative assessment of histological parameters was performed using histopathological and immunohistochemical techniques. miRNA expression analysis was performed by quantitative real-time PCR. Results: Intense transmural mononuclear inflammatory infiltrates in TAB-positive GCA arteries were predominantly composed of CD3+, CD4+ and CD8+ T lymphocytes, and CD68+ macrophages, accompanied by a strong nuclear overexpression of the nuclear factor of activated T cells, cytoplasmic 1 (NFATC) in the lymphocyte infiltrate fraction. Furthermore, TAB-positive GCA arteries were characterized by significant overexpression of nine pro-inflammatory miRNAs (miR-132-3p/-142-3p/-142-5p/-155-5p/-210-3p/-212-3p/-326/-342-5p/-511-5p) and a significant under-expression of six regulatory immune-related miRNAs (miR-30a-5p/-30b-5p/-30c-5p/-30d-5p/-30e-5p/-124-3p), whose expression levels significantly associated with most evaluated histopathological parameters. Notably, we revealed miR-132-3p/-142-3p/-142-5p/-155-5p/-212-3p/-511-5p as major promoters of arterial inflammation and miR-30a-5p/-30c-5p/-30d-5p as putative regulators of NFATC signaling in TAB-positive GCA arteries. Conclusion: Overall, we demonstrated that an altered arterial tissue-specific pro-inflammatory miRNA signature favors enhanced T cell-driven inflammation and macrophage activity in TAB-positive GCA arteries. Moreover, dysregulation of several immune-related miRNAs seems to contribute crucially to GCA pathogenesis, through impairing their regulatory activity towards T cell-mediated immune responses driven by the calcineurin (CaN)/NFAT signaling pathway, indicating their therapeutic, diagnostic and prognostic potential.